Workplace spirituality and the affective commitment : emotional intelligence as moderator - Syahrizal; Miftahul Khaira (Human Resource Management Studies, 2021)
The purpose of this study were to analyze the relationship between workplace spirituality and affective commitment when emotional intelligence is a moderat or variable to Nurses at the RST Dr. Reksodwiryo Padang. The population in this study were all contract nurses in the inpatient department at the RST Dr. Reksodiwiryo Padang as many as 108 people. The number of samples used in the study was 85 people using the clusters proportional random sampling technique. The research design used in this study is causality research. The data analysis technique used is the Structural Equational Model (SEM) with the help of the SmartPLS 3.0 . The results of this study revealed that the emotional intelligence moderates the relationship was found to be significant to Nurses at the RST Dr. Reksodwiryo Padang.